Proceedings of the 2nd International Electronic Conference on Atmospheric Sciences 2017
DOI: 10.3390/ecas2017-04128
|View full text |Cite
|
Sign up to set email alerts
|

The Predictability of Northern Hemispheric Blocking Using an Ensemble Mean Forecast System

Abstract: Some weather extremes can be the result of atmospheric blocking, which can be responsible for the stagnation of weather patterns. These large-scale quasi-stationary mid-latitude flow regimes can result in significant temperature and precipitation anomalies in the regions that the blocking event impacts. The ability to predict periods of anomalous weather conditions due to atmospheric blocking is a major problem for medium-range forecasting. Analyzing the NCEP Ensemble 500-mb pressure heights (240 h) ten-day fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…The calculation for the correlation coefficient and the significance can be found in any introductory statistics text (e.g., [37]). However, if BI is lagged by 24 h, testing the assertion of [35,36], the correlation is 0.72, which is significant at the 99% confidence level supporting the possible lag relationship suggested by [35,36]. For the winter 2017 blocking case (Table 2), BI was relatively high for both the onset and intensification period, however, IRE did not increase markedly for 72 h following onset.…”
Section: Blocking Cases: Bi Ire Ksementioning
confidence: 67%
See 4 more Smart Citations
“…The calculation for the correlation coefficient and the significance can be found in any introductory statistics text (e.g., [37]). However, if BI is lagged by 24 h, testing the assertion of [35,36], the correlation is 0.72, which is significant at the 99% confidence level supporting the possible lag relationship suggested by [35,36]. For the winter 2017 blocking case (Table 2), BI was relatively high for both the onset and intensification period, however, IRE did not increase markedly for 72 h following onset.…”
Section: Blocking Cases: Bi Ire Ksementioning
confidence: 67%
“…They also showed that the central height value and, thus, BI continues to increase for a short period following upstream cyclogenesis. Then, the pilot study of [35] suggested that first cyclogenesis occurs and then IRE increases, followed by BI for four case studies, including the winter 2017 case here. Additionally, in order to attempt to explain the difference in the lag times for each case, the deepening rates of the upstream cyclones were calculated.…”
Section: Blocking Cases: Bi Ire Ksementioning
confidence: 94%
See 3 more Smart Citations